DIFFERENT CONCENTRATIONS OF AMMONIUM NITRATE (NH4NO3) AFFECT NITROGEN METABOLISM AND THE DEVELOPMENT OF Acmella oleracea L. (Asteraceae) GROWN IN VITRO (REMUNOM, 2025)
Nitrogen deficiency in leafy vegetables, such as Acmella oleracea, affects growth and plant metabolism, negatively impacting productivity. This study aimed to evaluate the nitrogen metabolism and development of A. oleracea cultivated in vitro under different concentrations of ammonium nitrate (NH₄NO₃). Seeds were germinated in MS medium with three sucrose concentrations (30 g L⁻¹ - T1; 20 g L⁻¹ - T2; 10 g L⁻¹ - T3) and subjected to biometric analysis after 4 weeks. No significant differences were observed in the biometric variables for the number of leaves and root length, except for shoot length and fresh weight in the medium with 30 g L⁻¹ of sucrose. In the micropropagation stage, shoot tips were cultivated in basic MS medium (T1), MS with ½ NH₄NO₃ (T2), and MS with 2x NH₄NO₃ (T3), all supplemented with 0.4 mg L⁻¹ of BAP. After 4 weeks, biometric measurements and biochemical analyses were performed. T1 exhibited critical development, while T1 and T3 showed callus formation at the base of the explants, hindering root formation. In T3, a significant increase was observed in nitrate (26.52%), free ammonium (150.68%), and amino acid (94.12%) levels, accompanied by a 20.7% reduction in total soluble carbohydrates. The use of 0.4 mg L⁻¹ of BAP caused toxicity in A. oleracea plants. Increased nitrogen concentrations in the form of NH₄NO₃ may lead to reduced carbon metabolism. Therefore, appropriate ammonium nitrate concentrations should be adjusted to optimize the development of A. oleracea cultivated in vitro.